Association between hepatoblastoma and polyposis coli. Issue 12 (December 1983) - Kingston, J E; Herbert, A; Draper, G J; Mann, J R
Abstract : We have identified five children with hepatoblastoma who have a family history of polyposis coli affecting the mother and maternal relatives. We believe that the familial association of these two conditions is unlikely to have occurred by chance. Cytogenetic studies on three of the families have shown no evidence of a chromosomal abnormality.